K-State Turfgrass Research 2007 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Turfgrass Research 2007 contains results of projects done by K-State faculty and graduate students. Some of these results will be presented at the Kansas Turfgrass Field Day, August 2, 2007, at the Olathe Extension and Research Center. The enclosed articles present summaries of research projects that were completed recently or will be completed in the next year or two. Specifically, this year’s report presents summaries of research on environmental stresses, turfgrass establishment and culture, and cultivar evaluations.
Keywords: Turfgrass; Disease Control; Environmental Stress; Fertilization; Tall Fescue; Bluegrass; Bermudagrass